Associations of long-term exposure to air pollution, physical activity with blood pressure and prevalence of hypertension: the China Health and Retirement Longitudinal Study - Zhang, Jinglong; Zhang, Fen; Xin, Chao; Duan, Zhizhou; Wei, Jing; Zhang, Xi; Han, Shichao; Niu, Zhiping (Frontiers in Public Health, 2023)
Background: Exposure to higher concentration of air pollution and low physical activity are associated with elevated blood pressure levels and prevalence of hypertension. However, their joint effects are still unknown. Methods: A total of 14,622 middle-aged and older adults from the China Health and Retirement Longitudinal Study wave 3 were included in this study. Ambient air pollution (particulate matter with diameter ≤2.5 µm (PM2.5), or ≤ 10 µm (PM10), sulfur dioxide (SO2), nitrogen dioxide (NO2), carbonic oxide (CO)) were estimated using satellite-based spatiotemporal models. Physical activity was investigated using International Physical Activity Questionnaire. Generalized linear models were used to examine the associations of air pollution, physical activity score with blood pressure (systolic blood pressure (SBP), diastolic blood pressure (DBP) and mean arterial pressure (MAP)) and the prevalence of hypertension. Subgroup analysis by different physical activity groups was conducted to examine whether physical activity could modify the effects of air pollution on blood pressure and prevalence of hypertension. Results: Exposure to higher concentration of PM2.5, PM10, SO2, NO2, CO and lower physical activity were associated with increased SBP, DBP and MAP levels and prevalence of hypertension. Higher level of physical activity was associated with decreased SBP, DBP and MAP levels and prevalence of hypertension. Subgroup analysis found that the estimated effects in sufficient physical activity group was lower than that among insufficient physical activity group. Conclusion: Exposure to high-level air pollutants and low-level physical activity are associated with increased blood pressure and prevalence of hypertension. Strengthening physical activity might attenuate the adverse effects of air pollution on blood pressure and hypertension risk.